Influence of litter source on soil splash rates and organic carbon loss in different soil horizons - Parwada, Cosmas; Van Tol, Johan (Water SA, 2019)
Organic litter stabilizes soil particles against the raindrop splash effect. To date, limited research has critically examined the effects of litter quality on soil aggregate detachment and soil organic carbon loss by raindrop splash impact. A study was conducted to determine the effects of different litter sources on quantity of splashed sediments and soil organic carbon (SOC) loss under simulated rainstorm patterns. Soils from seven sieved (< 0.25 mm) horizons mixed with either high-quality Vachellia karroo leaf (C/N = 23.8) and/or low-quality Zea mays stover litter (C/N = 37.4) were incubated in a laboratory for 30 weeks. Splashed sediments and SOC were measured at 1, 3, 8, 14, 23 and 30 weeks of incubation for each soil at 360 mm/h simulated rainfall intensity applied as either single 8-min rainstorm (SR) or 4 × 2-min intermittent rainstorms (IR) separated by a 72-h drying period. Organic litter significantly (P < 0.05) reduced the splashed sediments up to 8 and 14 weeks under IR and SR storms, respectively, and thereafter gradually lost its stabilizing effect on soil aggregates. In order to maintain low quantities of splashed sediments, fresh litter has to be re-applied after this stage. Generally, 13% and 25% more sediments were splashed under IR than SR at 1, 3 and 30, and 8, 14 and 23 weeks after incubation, respectively. Litter quality effect on splash sediments varied across soil horizons but were the same within a soil horizon. Soil horizons with more clay than sand particles had lower quantities of sediments. The SOC loss was influenced by the initial SOC content and primary particle size distribution. Rainstorm pattern and initial SOC content were the main factors that influenced SOC loss. However, more rainstorm patterns should be investigated for these soils.